An analysis of thai commercial banks branch expansion factors including leadership, location, cost and economics - Meesrichan, Sittichai; Fongsuwan, Wanno (My University, 2014)
A bank is a financial institution which deals in debts and credits. It accepts deposits, lends money and creates money. The global financial system is the worldwide framework of legal agreements, institutions and formal and informal economic actors that together facilitate international flows of financial capital for purposes of investment and trade financing. Effects of globalization make the movement of funds a requirement for many businesses, which includes Thai commercial banks' foreign investors. Foreign influence on Thai commercial banking has affected the management, style and size of the locations and branches. Additionally, scheduled branches openings are not happening due to various factors including external economic factors affecting the organization's performance, Return On Investment (ROI), amount of loan losses and the ratio of capital to risk-weighted assets of the bank. External factors included GNP (Gross National Production), export value and the savings/spending levels of local consumers. These economic factors will affect the organization's strategy and the commercial banks' strategic planning and staffing for expansion and influence location choice, branch cost and size. Consumer behavior, population density and demographics of the selected community are also external factors. Other factors include implemented transaction technologies and the potential for future expansion. Findings of this study concluded that the location and cost did not influence the branch expansion in Thailand, but it is a factor that is influenced by corporate leaders. Banks need to add branches and more service points.
Keywords: Banks; Branch expansion; Cost; Economics; Financial; Leadership